Measuring the impacts of celebrity endorsement on consumers’ behavioural intentions: a study of consumers from Nestlé Products Sdn Bhd - Abdul Samad, Ikmal Annur-Hyffny (2019)
This study is conducted to explore the impact of celebrity endorsement on consumers’ behavioural intentions with source attractiveness, source trustworthiness, source expertise as well as the fit between the endorser and endorsed product in Nestle Products Sdn Bhd, Mutiara Damansara. The data has been collected from 97 respondents with the help of structured questionnaire and analysed by using the Statistical Package for Social Science software version 22.0. There are four independent variables which are source attractiveness, source trustworthiness, source expertise and the fit between endorser and endorsed products and a dependent variable which is consumers’ behavioural intentions. Previous researchers indicated that source attractiveness, source trustworthiness, and source expertise are crucial for the effectiveness of celebrity endorsement. The fit between endorser and endorsed product on the other hand does not bring into being significant. Nevertheless, it affects consumers’ behavioural intentions indirectly through source attractiveness, source trustworthiness, and source expertise. The researcher used probability sampling technique in selecting the targeted respondents for the study. This research is valuable to many sources in order to improve their strategies in increasing more potential consumers. Furthermore, this research also will be useful to marketers to improve their marketing approach on advertising with the help of celebrity endorsements.